Sex and consequences : abortion, public policy, and the economics of fertility - Levine, Phillip B. (Princeton University Press, 2004)
How do individuals change their behavior when abortion access increases? In this book, economist Phillip Levine compares abortion to a form of insurance, contending that abortion provides protection from downside risk. A pregnant woman who would otherwise give birth to an unwanted child has the option to abort. On the other hand, the availability of this option may increase the likelihood of a pregnancy in the first place. In a very restrictive abortion environment, few women would choose to have an abortion; legalizing abortion would reduce unwanted births. But if abortion becomes readily available, it may cause individuals to increase their sexual activity and/or reduce their use of contraception, Levine contends. Women will become pregnant more frequently, but will abort those pregnancies. Therefore, these abortions will not reduce unwanted births. Levine's analysis suggests that the manner in which individuals change their behavior depends on the extent to which abortion is accessible. He supports these assertions using data from both the United States and Eastern Europe, comparing areas that have restricted access to abortion services with those that have liberalized access. Using sound economic analysis, Sex and Consequences goes beyond the ideological arguments that frequently dominate the abortion debate, lending a new perspective to this controversial subject.